Hydrogen bond driven fluorescent lighting up for cysteine based on excited state intramolecular proton transfer process. (January 2022) - Guo, Xinjie; Wan, Chenyang; Li, Jiajia; Xiao, Yuzhe; Cao, Qilong; Zhang, Qian; Zhang, Peng; Ding, Caifeng
Abstract: Schiff base generated by salicylaldehyde processes a hydroxyl group in the ortho position usually shows the properties of excited state intramolecular proton transfer (ESIPT). The six membered intramolecular hydrogen bonding network in the ground state of the proton transfer center accelerates the ESIPT process. In this work, a readily synthesized non-emissive probe (probe 1, "Off state") for the detection of cysteine (Cys) was designed based on the nucleophilic addition and departure reactions of cysteine and acrylate. The released chromophore (DEASH) emitted bright green fluorescence ("On state") with a quantum yield of 36.23% due to the process of ESIPT induced by the intramolecular hydrogen bonding. The specific sensing reaction was infeasible for the other thiols (even glutathione (GSH) and homocysteine (HCy)) and contributed to a supreme selectivity for Cys. Probe 1 also provides a sensitive detection process for Cys in aqueous buffer with a relatively low detection limit of 36.4 nM. In addition, the probe can be used for fluorescence imaging of exogenous and endogenous Cys in living cells as well as zebrafish with low cytotoxicity. These advantages indicate that the probe has important practical value for the monitoring of Cys in biological systems. Graphical abstract: Image 1 Highlights: A readily synthesized non-emissive probe for the detection of Cys was designed. The chromophore emits green fluorescence due to the recovery of ESIPT process. The probe provides a selective detection process for Cys with a LOD of 36.4 nM. The probe can be used for fluorescent imaging of Cys in living cells and zebrafish.